Clasificación ecológica y caracterización selvícola y PRODUCTIVA DEL PARQUE NATURAL DE LOS ALCORNOCALES (CÁDIZ y MÁLAGA) - Torres Álvarez, E; Montero González, G; V ÁZQUEZ PIQUÉ, F J (II Congreso Forestal Español, 1997)
An ecological classification of the Natural Park "Los Alcornocales" (Cádiz and Málaga, Spain) and a silvicultural and productive characterisation are done. The territorial c1assification is assisted by a Geographical Information System. Sixteen Territorial Classes and five classes of cork-oak potentiality are defined and mapped. Using a sample of seventy two plots, the cork-oak forests of this area are silvicultural and productively characterised, according their Territorial Class.
Keywords: Cork; cork-oak; Ecological classification; Geographical inforn1ation system; Potentiali ty; Quercus suber

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E Torres; González, G Montero; Suárez, M A; Cámara, D E L A; Torres Álvarez, E; Montero González, G; Suárez de la Cámara, M A (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
Keywords: cork-oak; Quercus suber; silviculture; stand density

Seguimiento de la regeneración natural de alcornoque bajo condiciones microecológicas diferentes. - Torres Álvarez, E; Montero González, G; de la cámara, m. a. (II Congreso Forestal Español, 1997)
This paper studies the natural regeneration of cork-oak in the forests of Aljibe mountains (Málaga, Spain). A plot for monitoring the development of cork-oak seedlings was installed at Cortes de la Frontera cork-oak forests, under different microecological conditions. To get a plentiful and healthy stock of seedlings is necessary enclose the area and to have a light crown cover, is the main conclusion.
Keywords: cork-oak; natural regeneration; Quercus suber; Sylviculture